Minimally invasive reoperation through a lateral thoracotomy for circumflex coronary artery bypass. - Coulson, A S (1998)
We report 4 cases of redo coronary artery bypass grafting in which the circumflex coronary artery was successfully revascularized using a minimally invasive approach. In reoperative cases, it is easier to approach the circumflex coronary artery from the left side than from the front. Minimally invasive direct coronary artery bypass technology has made it possible to avoid using cardiopulmonary bypass. In our 4 cases, the revascularization procedure was performed via a small left thoracotomy, and without cardiopulmonary bypass. The patients made a good recovery and are free of angina 22 months after operation. We conclude that the thoracotomy approach provides the opportunity to avoid several hazards: a redo sternotomy, dissection of a hostile mediastinum, and manipulation of the heart.